2007
DOI: 10.1159/000109715
|View full text |Cite
|
Sign up to set email alerts
|

Role of MMP-1 1G/2G Promoter Gene Polymorphism on the Development of Prostate Cancer in the Turkish Population

Abstract: Introduction: To investigate the association of 1G/2G polymorphism in matrix metalloproteinase-1 (MMP-1) promoter with susceptibility to prostate carcinoma in the Turkish population. Materials and Methods: MMP-1 promoter polymorphism was genotyped by PCR-RFLP analysis in 55 prostate cancer patients and 43 healthy controls. Results: The frequency of 1G/2G genotypes in prostate cancer patients was similar to that of the controls (all p values were >0.05). Compared with the 1G/1G genotype, neither the 2G/2G nor a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 21 publications
2
22
2
Order By: Relevance
“…There is only one small-scale study regarding prostate cancer, which showed that the MMP-1 promoter polymorphism was not associated with susceptibility to the disease (29). Our relatively large-scale study also did not find any association with susceptibility to prostate cancer.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…There is only one small-scale study regarding prostate cancer, which showed that the MMP-1 promoter polymorphism was not associated with susceptibility to the disease (29). Our relatively large-scale study also did not find any association with susceptibility to prostate cancer.…”
Section: Discussioncontrasting
confidence: 77%
“…In prostate cancer, immunohistochemical and in situ hybridization analysis have detected MMP-1 in cancer cells as well as in normal adjacent and prostatic intraepithelial cells (28). However, a previous study that evaluated the effect of the polymorphism on prostate cancer found no association between MMP-1 and susceptibility or metastatic status of prostate cancer (29). There have been few studies focusing on the clinical implication of MMP-1 expression, promoter polymorphism, and allelic imbalance (AI) of 11q22.…”
Section: Introductionmentioning
confidence: 99%
“…There were eight articles, including 1689 cancer cases and 1690 controls, for the MMP1 -1607 1G/2G SNP (four about bladder cancer, two about prostate cancer, and two about renal cell carcinoma); four articles, including 1020 cancer cases and 960 controls, for the MMP2 -1306 C/T SNP; three articles, including 838 cancer cases and 735 controls, for the MMP9 -1562 C/T SNP; two articles, including 440 cancer cases and 399 controls, for the MMP7 -181 A/G SNP; three articles, including 907 cancer cases and 942 controls, for the MMP9 (279R/Q) A/G SNP; two articles, including 726 cancer cases and 737 controls, for the MMP3 (45E/K) G/A SNP; two articles, including 756 cancer cases and 760 controls, for the MMP9 (574R/P) T/C SNP; and two articles, including 745 cancer cases and 745 controls, for the MMP9 (668Q/R) A/G SNP. The distribution of genotypes among the control samples was consistent with HWE in all studies except four: Kader et al (2006), Albayrak et al (2007), Srivastava et al (2010b), and Wieczorek et al (2013). Polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP), DNA sequencing, and TaqMan Ò Real-Time PCR were used as genotyping methods in all publications.…”
Section: Eligible Studiesmentioning
confidence: 84%
“…We also found only one Chinese article in the WanFang database. As a result, 12 case-control articles were included in our meta-analysis: (Hirata et al, 2004;Zhong et al, 2005;Kader et al, 2006;Albayrak et al, 2007;Piccoli et al, 2007;Tasci et al, 2008;Tsuchiya et al, 2009;Srivastava et al, 2010aSrivastava et al, , 2010bWieczorek et al, 2013Wieczorek et al, , 2014Srivastava et al, 2013a) (Fig. 1).…”
Section: Eligible Studiesmentioning
confidence: 99%
See 1 more Smart Citation